2015
DOI: 10.4209/aaqr.2015.03.0132
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Aerosol Extinction Coefficient in Taipei Metropolitan Atmosphere

Abstract: The object of this study investigated the correlation of visibility with aerosol physical properties in the urban atmosphere. The field experiments were conducted in four seasons from August 2010 to March 2011 in National Taipei University of Technology (NTUT), located in the downtown of Taipei city. Integrating nephelometer was used to measure the aerosol optical properties and compared with the calculated values based upon the measurements of aerosol concentration and size distribution. The characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Suspended PMs in the atmosphere play a vital role on the physical, chemical, and optical effects, such as ambient air quality, atmospheric visibility, and radiative forcing (Claiborn et al 2011;Tsai et al 2010;. Poor atmospheric visibility is highly related to PMs, resulting from the extinction of visible light by fine particles (Cheng et al 2015). Moreover, such natural fugitive dust could also cause health problems if fine particles existed in connection with coarse particles suspended in the air.…”
Section: Introductionmentioning
confidence: 99%
“…Suspended PMs in the atmosphere play a vital role on the physical, chemical, and optical effects, such as ambient air quality, atmospheric visibility, and radiative forcing (Claiborn et al 2011;Tsai et al 2010;. Poor atmospheric visibility is highly related to PMs, resulting from the extinction of visible light by fine particles (Cheng et al 2015). Moreover, such natural fugitive dust could also cause health problems if fine particles existed in connection with coarse particles suspended in the air.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that the atmospheric visibility is related to PM (Pillai et al, 2002;Pui et al, 2014;Cheng et al, 2015). The higher the particle mass concentration is, the poorer the visibility is (Kim et al, 2001;De et al, 2005;Cheng et al, 2015). At the same time, dust emission also influences the regional air quality and bring about human health problems (Ono, 2006;Goudie, 2009;Rashki et al, 2013;Goudie, 2014), especially, the contaminants along with dust affect human health as its transport to the densely populated town or city.…”
Section: Introductionmentioning
confidence: 99%
“…In general, pool visibility is essentially assigned to the extinction of visible light by particles (Friedlander, 2000). Several studies reported that the atmospheric visibility is related to PM (Pillai et al, 2002;Pui et al, 2014;Cheng et al, 2015). The higher the particle mass concentration is, the poorer the visibility is (Kim et al, 2001;De et al, 2005;Cheng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%